KUALITAS POLITUR ORGANIK DARI EKSTRAK KAYU JATI DAN SIRLAK - Jamal Balfas (BRIN Publishing, 2017)
Currently, commercial wood finish products are predominantly chemical solvent-based, such as melamine formaldehyde and nitrocelulose. Although these products give desirable quality, durable and affordable cost, their volatile organic compounds are detrimental to the environmental and harmful to the health. This paper studies the use of teak extract mixed with shellac as alternative top coat or wood stain. Quality of the alternative formula was tested on tusam and rubber wood by assessing their physical, mechanical and chemical performances in comparison with the commercial products, i.e. melamine formaldehyde (MF) and nitrocellulose (NS). Samples of two wood species were treated by dipping them in various wood finishing solutions. Weight and dimensional changes due to the treatment were determined in wet and dry sample conditions. Results showed that weight and dimensional gains due to dipping treatment were varied according to wood species, grain orientation and finishing solution. Tusam samples possed greater weight and dimensional gains than those of rubber wood samples. All organic finishing formulas were able to protect wood from water intrution, however they were less effective than the commercial MF and NS. Top coat made from the mixture of teak extract and shellac has lower scratch resistance and less resistant against chemical liquids than the commercial MF and NS. Wood stain of teak extract and shellac mixture provided better color value than the commercial wood stain in term of color likeness to the true teak.